2009
DOI: 10.1007/s10689-009-9241-0
|View full text |Cite
|
Sign up to set email alerts
|

PALB2 sequence variants in young South African breast cancer patients

Abstract: PALB2 (partner and localizer of BRCA2) is a recently identified breast cancer susceptibility gene, in which mutations confer doubling of breast cancer risk with moderate to low penetrance. Recent studies in various populations report that deleterious mutations in this gene account for approximately 1% of familial or early-onset breast cancer cases. This study aimed to determine the involvement of PALB2 mutations in a cohort of 48 young (29-45 years) South African breast cancer patients unselected for family hi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
26
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 48 publications
(31 citation statements)
references
References 26 publications
5
26
0
Order By: Relevance
“…Many studies previously reported that mutations in the PALB2 gene showed evidence of being correlated with a significantly increased risk of breast cancer [9,10,11,12], especially hereditary breast cancer [13,14]. Mutations in the PALB2 gene confer a doubled breast cancer risk with moderate-to-low penetrance [15]. Our previous meta-analysis also indicated that polymorphism in the PALB2 gene locus rs249954 was associated with breast cancer risk, and we already demonstrated that a heterozygous (CT) genotype in PALB2 gene locus rs249954 increases breast cancer susceptibility (table 8) [7].…”
Section: Discussionmentioning
confidence: 99%
“…Many studies previously reported that mutations in the PALB2 gene showed evidence of being correlated with a significantly increased risk of breast cancer [9,10,11,12], especially hereditary breast cancer [13,14]. Mutations in the PALB2 gene confer a doubled breast cancer risk with moderate-to-low penetrance [15]. Our previous meta-analysis also indicated that polymorphism in the PALB2 gene locus rs249954 was associated with breast cancer risk, and we already demonstrated that a heterozygous (CT) genotype in PALB2 gene locus rs249954 increases breast cancer susceptibility (table 8) [7].…”
Section: Discussionmentioning
confidence: 99%
“…In total, 77 PALB2 mutation-positive cases have been identified mainly in familial or early onset breast cancer cohorts from different populations [13,15,[18][19][20][21][22][23][24][25]. Of the 77 described PALB2 mutation cases, 52 are carrier of the 1592delT Finnish founder mutation, which could influence the currently known phenotype [19,24,26].…”
Section: Discussionmentioning
confidence: 99%
“…According to different ethnic reports [95][96][97][98][99][100] , about 1% of women with early-onset BCs negative for BRCA1/2 mutations carry a mutation in this gene.…”
Section: Palb2mentioning
confidence: 99%